Finding a Fingerprint. Microtiming and Tempo Variability in Five Renowned Rock Drummers - Carter, David; von Appen, Ralf (Revue musicale OICRM, 2025)
In this article, we analyze microtiming and tempo variability in the music of five renowned rock drummers: Ringo Starr, Mitch Mitchell, Stewart Copeland, Phil Rudd, and Meg White. Using the applications Moises and Sonic Visualiser, we isolated the drum stems of 79 studio and live recordings and determined exact quarter-note positions in backbeat patterns. We used metrics such as the normalized absolute deviation beat sum, average beat coefficient of variation, and tempo coefficient of variation in order to capture these drummers’ distinctive “fingerprints.” We found that Starr showed a propensity for delayed backbeats and slowing down, Copeland a tendency for early backbeats, Rudd steadiness without a click track, and Mitchell and White a propensity towards wide variability in timing and tempo. The results of this exploratory study suggest that drumming characteristics are shaped not only by personal style but also by broader historical trends.